1988
DOI: 10.1139/z88-223
|View full text |Cite
|
Sign up to set email alerts
|

The Gusum case: a brass mill and the distribution of soil Collembola

Abstract: BENGTSSON, G., and RUNDGREN, S. 1988. The Gusum case: a brass mill and the distribution of soil Collembola. Can. J. Zool. 66: [1518][1519][1520][1521][1522][1523][1524][1525][1526]. The sensitivity towards metal pollution of some population and community characteristics in Collembola was demonstmted based on observations at eight field sites along a transect from a brass mill. Samples were collected in coniferous forest soils at Gusum, southeastern Sweden, where a local brass mill has created a metal gradient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1
4

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(41 citation statements)
references
References 24 publications
5
31
1
4
Order By: Relevance
“…In the region polluted by the copper smelting works at Gtog6w, a high concentration of heavy metals reduced the density and species number of mites. This is consistent with the results that Bengtsson and Rundgren (1988) obtained in coniferous forests polluted by a brass mill at Gusum (Sweden), and H~gvar and Abrahamsen (1990) observed in Norwegian forests naturally polluted by lead.…”
Section: Discussionsupporting
confidence: 92%
“…In the region polluted by the copper smelting works at Gtog6w, a high concentration of heavy metals reduced the density and species number of mites. This is consistent with the results that Bengtsson and Rundgren (1988) obtained in coniferous forests polluted by a brass mill at Gusum (Sweden), and H~gvar and Abrahamsen (1990) observed in Norwegian forests naturally polluted by lead.…”
Section: Discussionsupporting
confidence: 92%
“…et al, 1997;Smit, 1997;Van Straalen et al, 1989). This was re#ected in the "eld where Collembola collected from around a brass mill in SE Sweden were found to have much greater IBCs closer to the source of contamination (Bengtsson and Rundgren, 1988). The concentration factor (Table 4) of metal (except Pb) in the animals decreased as exposure concentrations increased.…”
Section: Internal Body Concentrationsmentioning
confidence: 92%
“…Consequently there is concern regarding the e!ects of toxicants including metals on soil fauna (Bruce et al, 1997(Bruce et al, , 1999. In metal-contaminated soils a decrease in the density and sometimes diversity of Collembola is known to occur, concomitant with a decrease in the rate of decomposition of the litter layer Bengtsson and Rundgren, 1988;Hopkin, 1994). While some authors have reported changes in species assemblages as the main e!ect of metals on Collembola in soil (Bruce et al, 1997;Filser and HoK lscher 1997;Ha s gvar and Abrahamsen, 1990;LuK bben, 1989;NuK ss, 1994;Williamson and Evans, 1973), other workers have found di!erences in the abundances of Collembola at metal-contaminated sites, with fewer springtails occurring closer to the source of pollution (Haimi and Siirapietikainen, 1996;Kuznetsova and Potapov, 1997;Strojan, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…These include studies undertaken to quantify community change in major invertebrate groups along metal contamination gradients [7,56], as well as studies with specific soil taxa like earthworms [57][58][59], springtails [8,60], mites [61], ground beetles [62] and spiders [63]. Changes observed in these studies included reduced overall abundance (including the presence of deserts for some groups), lower diversity as assessed using traditional metrics, altered community composition and changes in species dominance structure [64].…”
Section: Populations and Communitiesmentioning
confidence: 99%